Structural analyses of polyanilinetitanium oxide composite for acetone detection - Bahru R.; Zamri M.F.M.A.; Shamsuddin A.H.; Mohamed M.A. (Springer, 2023)
Acetone; Aniline; Chemical sensors; Fourier transform infrared spectroscopy; Gas detectors; High resolution transmission electron microscopy; Magnetic semiconductors; Scanning electron microscopy; Temperature; Titanium dioxide; Composite pellets; Operating temperature; Polyanilines (PAni); Scanning electrons; Semiconductor gas sensors; Sensing performance; Situ chemical polymerizations; Structural characterization; Polyaniline